The Role Of Bloom Taxonomy In Consistent Teaching Of English - Farmonova, Naimakhon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
Currently, higher education in Uzbekistan is going through a period of unprecedented changes. Undoubtedly, the main factor of these changes is the impact of innovative technologies on the educational process. Recognition of learning foreign languages as a priority direction of education policy in our country, improvement of the process of training future English language teachers, regular improvement of the quality and level of teaching foreign languages, in order to master the requirements for graduates that meet national and world standards.